A qualitative investigation into the impact of domestic abuse on women’s desistance - Barr, Úna (Probation journal, 2019)
While criminological literature, criminal justice practice, and to a lesser extent, state policy have acknowledged a link between women’s criminalisation and gendered violence (MoJ, 2018; Österman, 2018; Prison Reform Trust, 2017; Roberts, 2015), there has been much less acknowledgement of the role of historical and contemporaneous experiences of violence in the desistance scripts of criminalised women. Combining findings from two research projects exploring gender and desistance, this article argues that (i) criminalised women’s experiences of gendered violence are such that any exploration of gender and desistance which does not acknowledge this is incomplete, (ii) coercion and control can inform women’s entry into the criminal justice system, (iii) expressions of agency and resistance in abusive interpersonal relationships can also inform women’s offending, yet (iv) women’s experiences of desistance from crime can mask the harm they face in coercive, controlling, and violent relationships. Thus, the article argues for a reframing of desistance from crime as desistance from harm both theoretically and in practice, and considers what this might entail.